Galtonosides A-E: Antiproliferative and Antiplasmodial Cholestane Glycosides from Galtonia regalis - Du, Yongle (J Nat Prod, 2020)
An extract of Galtonia regalis from the Natural Products Discovery Institute showed moderate antiplasmodial activity, with an IC(50) value less than 1.25 μg/mL. The two known cholestane glycosides 1 and 2 and the five new cholestane glycosides galtonosides A-E (3−7) were isolated after bioassay-directed fractionation. The structures of the new compounds were determined by interpretation of their NMR and mass spectra. Among these compounds, galtonoside B (4) displayed the most potent antiplasmodial activity, with an IC(50) value of 0.214 μM against the drug-resistant Dd2 strain of Plasmodium falciparum.